EMPOWERING INTERNATIONAL COOPERATION'S ROLE IN THE FOLLOW OF ASSETS OF CORRUPTION'S RESULT - Arifin, Ridwan (UI Scholars Hub, 2014)
Corruption case no longer involves one party or one nation alone, but also involves many parties, too few countries. Corruption is no longer the case as an individual activity but a pattern of activity patterns and very organized group. Corruption is not just a question of a nation, but also the whole issue of the nations of the world. In the casse of corruption, repression is not only a top priority in the effort bondage and punishment, but also a return on assets of the most important things to do. The effort or corruptor impoverishment through seizure of assets is often hampered in practice, whether it intersect due to international cooperation, and asset tracking models. Asset tracking assessed include broader search than money, because the pattern of money laundering is now not only in money but also other assets that are the result of corruption and or benefits resulting from the corruption